KEADILAN ORGANISASI SEBAGAI VARIABEL MEDIASI ANTARA KOMUNIKASI ORGANISASI DENGAN KEPUASAN KERJA KARYAWAN PT. TELKOM SURABAYA - AZHARIMAN, HATIF (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: This study aims to evalute the organizational communication, job satisfaction, and organizational justice in PT. Telkom Surabaya Region employees. This study used stratified random sampling with the sample of 86 respondents. Methods of the statistical analysis that used were SEM Partial Least Square (PLS) with SMART PLS 2.0 software. The major finding of this study is there is an influence on the organizational communication and organizational justice. Based on the influence coefficient, it suggests that organizational justice is a mediator of the influence of organizational communication on employees’ job satisfaction. Keywords: organizational communication, organizational justice, and employees’ job satisfaction